IMPLEMENTASI KURIKULUM 2013 DALAM MEMBENTUK KARAKTER ANAK BANGSA - HM. Zainuddin, (UNIVERSUM: Jurnal Keislaman dan Kebudayaan, 2022)
In the last decade, our conscience has been disturbed by widespread violence that occurred in the society. A various form of vandalism and cruelty became a tragic phenomenon that is very easily seen in our country. Wisdom and magnanimity that had ever been exalted and glorifi ed as the character and identity of our nation has been today fossilized into niche of civilization. Therefore, there is a need for fundamental change in education of all levels, from kindergarten to high schools, for which curriculum restructuring is one option. In this sense, the application of curriculum 2013 has to be tailored to the needs of students and society. Curriculum 2013, which is a further development of competence based curriculum initiated in curriculum 2004 and 2006 (KTSP), includes also attitudes competence, knowledge, and skills simultaneously. This article attempts to examine the application of curriculum 2013 (K13) in school-learning process.